A comparative analysis of the effects of drop set and traditional resistance training on anaerobic power in young men - Fatma Tokat; Kadir Keskin (Turkish Journal of Kinesiology, 2023)
Drop set is a popular time-efficient resistance training method. This study aimed to compare the impact of drop-set (DS) training versus traditional resistance training (TRT) while ensuring equalized total training volume on the Wingate Anaerobic Test. Twenty-four sports science students were assigned to either DS (n=12) or TRT (n=12) protocols according to their 1 RM values, and they trained twice a week for 6 weeks.1 RM test was only conducted at the beginning of the study, while the Wingate anaerobic power test was administered at baseline and after the intervention period. The study demonstrated a significant main effect of time for peak power (p< 0.001), and a between-group interaction effect was observed for peak power (p< 0.05). The DS group exhibited slightly higher peak power values compared to TRT (p< 0.05, 15% increase for DS, 13% for TRT, ES: 0,50 and 0,36 respectively), while both groups displayed significantly increased values from pre to post-testing (p < 0.001). Based on our findings, it can be inferred that DS training leads to slightly greater enhancements in anaerobic power when compared to TRT. Additionally, the study confirmed that a 6-week (12 sessions in total) resistance training program utilizing a load of 70% of 1 RM was sufficient to enhance anaerobic performance in young active men.